Methodological foundations for the integrated assessment of the factors and level of human capital development in the region - V. V. Matveev; S. A. Ilminskaya; I. S. Efimenco (Вестник Северо-Кавказского федерального университета)
Introduction. Human capital is formed under the inﬂuence of socio-economic factors and it acts itself as an indicator of the development level in regions. On the other hand, it also inﬂuences the formation of the socio-economic environment, and its spatial asymmetry leads to uneven development in individual territories. Therefore, the state of reproduction and growth conditions, their coordination with the imperatives of the modern society development will contribute to the generation of strategically important measures aimed at the formation of high quality human capital.Goal. We aim to identify the priority areas for the capitalization of human capital based on the assessment of factors and the level of its development in the regional dimension.Materials and methods. The authors analysed the regional conditions of formation, the level of development and capitalization of human capital using the general scientiﬁc methods, the comparative analysis, the empirical generalization, the index method and the balanced scorecard method.Results and discussion. The article substantiates a methodological approach to the integrated assessment of factors and the level of development of regional human capital based on a system of balanced indicators. The paper also justiﬁes the possibility of its structural decomposition based on the requirements that apply to its quality in the context of digital transformation, the introduction of artiﬁcial intelligence technologies in all sectors of the economy and social sphere.Conclusion. The obtained results demonstrate the loss of human capital reserves in the region and emphasize the importance of the conditions that form the educational and cultural component.